2001
DOI: 10.1080/08927010109378483
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental factors on the rate and extent of stainless steel ennoblement mediated by manganese‐oxidizing biofilms

Abstract: The increase in the open circuit potential of passive metals in natural waters due to biofilm formation at the metal surface, termed ennoblement, has been reported for nearly 30 years. Although its occurrence is undoubtedly associated with microbial colonization, the underlying mechanism of ennoblement remains controversial. Recent work produced in the authors' laboratory has provided convincing experimental evidence that ennoblement can be caused by deposition of biomineralized manganese produced by manganese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In the domain of microbial corrosion of steels, a monospecies model has been implemented in river waters with Leptothrix discophora (Shi et al, 2002). It was thus confirmed that cycling of manganese ions may be an important pathway of oxygen reducing catalysis, particularly in waters that contain a high concentration of manganese ions (Braughton et al, 2001). The same experimental model was then proposed to design MFC biocathodes (Rhoads et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the domain of microbial corrosion of steels, a monospecies model has been implemented in river waters with Leptothrix discophora (Shi et al, 2002). It was thus confirmed that cycling of manganese ions may be an important pathway of oxygen reducing catalysis, particularly in waters that contain a high concentration of manganese ions (Braughton et al, 2001). The same experimental model was then proposed to design MFC biocathodes (Rhoads et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…Much research has been carried out in the domain of marine biocorrosion to explain the oxygen-reduction catalytic properties of seawater biofilms (Erable et al, 2012). It has pointed out a huge number of possible mechanisms, which can be roughly organized into three main groups: i) direct catalysis by extracellular compounds that are excreted by the cells and retained against the material surface by the biofilm matrix: extracellular enzymes (Lai and Bergel, 2000;Faimali et al, 2011;Erable et al, 2012), hemin (Iken et al, 2008), or quinone-based compounds (Freguia et al, 2010) have, for instance, been suspected of playing this role; ii) indirect catalysis mediated by metabolites, hydrogen peroxide (Landoulsi et al, 2008), or manganese oxide (Braughton et al, 2001); iii) and miscellaneous mechanisms, such as local acidification inside the biofilm, modification of the oxide layer properties of stainless steels, influence of light, etc., which are less often mentioned. Fig.…”
Section: Monospecies Vs Multispecies Biofilmsmentioning
confidence: 99%
“…A large experimental campaign demonstrated that the concentration of manganese ions directly influenced the rate of ennoblement, whereas the concentration of dissolved oxygen had no significant effect. [74]…”
Section: Indirect Catalysis Mediated By Hydrogen Peroxide Produced Bymentioning
confidence: 99%
“…If manganese-oxidizing biofilms are deposited on surfaces of passive metals, the potential of these metals increases in a process called ennoblement ( , ). It has been demonstrated that biomineralized manganese oxides can affect the rates and the mechanisms of electrochemical reactions ( ), leading to microbially influenced corrosion of metals. When corrosion coupons made of 316 L stainless steel were left immersed in a freshwater creek, the open circuit potential of the coupons increased from −50 mV to +400 mV SCE ( ).…”
Section: Introductionmentioning
confidence: 99%